The image of the hero in modern Ukrainian cinema. Interview with Natalka Vorozhbyt - Tymoshenko, Alyona (Ukrainian Cultural Studies, 2025)
Natalia Vorozhbyt is a Ukrainian writer, playwright, director, and screenwriter. She belongs to the “new drama” movement. She is a laureate of the Women In Arts Award in 2020, the State Prize of Ukraine named after Oleksandr Dovzhenko in 2021 for her outstanding contribution to the development of Ukrainian cinema, and the Shevchenko National Prize in 2022.